2016
DOI: 10.1017/s095026881600159x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with increasing campylobacteriosis incidence in Michigan, 2004–2013

Abstract: This study was conducted to examine the incidence trend of campylobacteriosis in Michigan over a 10-year period and to investigate risk factors and clinical outcomes associated with infection. Campylobacter case data from 2004 to 2013 was obtained from the Michigan Disease Surveillance System. We conducted statistical and spatial analyses to examine trends and identify factors linked to campylobacteriosis as well as ecological associations using animal density data from the National Agricultural Statistics Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
4
7
0
Order By: Relevance
“…Our results sometimes support and sometimes conflict with prior research. Like a casecontrol study in Michigan, we find that ground beef purchases are associated with higher risk of campylobacteriosis (Cha et al, 2016). Importantly, we confirm findings of the only US nationwide case-control study that chicken prepared at home is not a major risk factor for campylobacteriosis (Friedman et al, 2004).…”
Section: Lessons Learnedsupporting
confidence: 82%
“…Our results sometimes support and sometimes conflict with prior research. Like a casecontrol study in Michigan, we find that ground beef purchases are associated with higher risk of campylobacteriosis (Cha et al, 2016). Importantly, we confirm findings of the only US nationwide case-control study that chicken prepared at home is not a major risk factor for campylobacteriosis (Friedman et al, 2004).…”
Section: Lessons Learnedsupporting
confidence: 82%
“…Campylobacter shed by cattle can also contribute to contamination of the environment via run-off water from farming and meat processing operations, which represent additional sources for human infections. One prior study found identical genotypes of C. jejuni recovered from dairy cattle and ground water (Kwan et al, 2008), while our study of 7,182 human campylobacteriosis cases in Michigan identified epidemiological associations between disease and contact with ruminants, well water, and living in a rural area with higher cattle densities (Cha et al, 2016a). …”
Section: Introductionmentioning
confidence: 56%
“…Human Campylobacter infections are primarily due to the handling and consumption of contaminated poultry products, with water and milk also serving as sources of infection ( 7 , 8 ). Molecular typing methods, including multilocus sequence typing and whole-genome sequencing, have been employed to better understand mechanisms of Campylobacter transmission from farm to fork ( 9 12 ).…”
Section: Genome Announcementmentioning
confidence: 99%